Analysis Of The Cooperation Of PT Pindad Bumn Bussiness Group In Increasing Umkm Productivity - Andes Pradana Kusumah; Sulaeman Rahman; Siti Chaerani Djen Amar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine the implementation of the operational cooperation program between PT Pindad Enjiniring Indonesia and PT Mikron Presisi Indonesia can increase the productivity of PT Mikron Presisi Indonesia. Knowing the supporting and inhibiting factors of the operational cooperation program between PT Mikron Presisi Indonesia and PT Pindad Enjiniring Indonesia. Then find out the impact of Operational Cooperation between PT Mikron Presisi Indonesia and PT Pindad Enjiniring Indonesia. This research uses qualitative methods with a descriptive approach. The process of data analysis in qualitative research is more focused during the process in the field along with data collection which includes data reduction, data presentation, and conclusion drawing/verification. The results showed that the operational cooperation carried out between PT.PEI and MSMEs, namely PT.MPI, has provided benefits and impacts for both parties, especially for PT.MPI. In this case, in addition, there are also supporting and inhibiting factors of operational cooperation between PT.PEI and PT.MPI. This research can provide new insights and knowledge for MSMEs and SOEs that will carry out operational cooperation. This study will look at the important things that need to be considered in conducting operational cooperation, supporting and inhibiting factors, and the benefits that can be obtained from operational cooperation. MSMEs and SOEs can use the results of this study to develop clearer schemes and rules regarding the operational cooperation mechanism that will be carried out, so that it can have a positive impact on both parties. Although the research provides an overview of the impacts resulting from operational cooperation between MSMEs and SOEs, the research has not highlighted and measured the level of effectiveness of the cooperation. Thus, research is needed in a longer period of time to see how the effectiveness of operational cooperation is carried out.